2023
DOI: 10.3390/app13106022
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model of Cancer Diseases Diagnosis Based on Gene Expression Data with Joint Use of Data Mining Methods and Machine Learning Techniques

Abstract: One of the current focuses of modern bioinformatics is the development of hybrid models to process gene expression data, in order to create diagnostic systems for various diseases. In this study, we propose a solution to this problem that combines an inductive spectral clustering algorithm, random forest classifier, convolutional neural network, and alternative voting method for making the final decision about patient condition. In the first stage, we apply the spectral clustering algorithm to gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In this study, we extend our previous research on the application of deep learning methods for gene expression data processing, aiming to develop and enhance cancer disease diagnosis systems [11][12][13]. The main contributions of the current research are as follows:…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we extend our previous research on the application of deep learning methods for gene expression data processing, aiming to develop and enhance cancer disease diagnosis systems [11][12][13]. The main contributions of the current research are as follows:…”
Section: Introductionmentioning
confidence: 92%
“…The gene expression value of a sample, as outlined in Table 1, signifies its activity level, indicative of the intensity of the associated protein synthesis process, and is proportionate to the volume of similar genes. In compliance with the methodology detailed in [11,13], firstly, absolute gene counts were converted into a more conducive range (Count Per Million-CPM) using the subsequent formula:…”
Section: Experimental Datasetmentioning
confidence: 99%
“…The plantar flexors (PF) correspond to the swing-leg pushing the center-of-mass forward, and the PF correspond to the stance-leg producing opposing torque. The study conducted in [ 8 ] demonstrated that the opposing forces produced by PF can persuade freezing, and it also explained the gait irregularities that are closer to freezing, such as step length reduction and irregular walking patterns.…”
Section: Related Workmentioning
confidence: 99%
“…They also include a convolutional autoencoder and transfer learning-based scheme for Alzheimer’s disease visualization [ 53 ]; a perceptron neural network for bacterial behavior programming [ 54 ]; and a deep neural architecture with generative adversarial network for brain tumor classification [ 55 ]. In addition, they include a deep neural network for epidemic prediction of COVID disease [ 56 ]; deep learning for sequential analysis of biomolecules [ 57 ]; elastic net and neural networks for the identification of plant genomics [ 58 ]; data mining and machine learning algorithms based on spectral clustering, random forest, and neural networks for cancer diagnosis through gene data [ 8 ]; and a stacking ensemble model based on an auto-regressive integrated moving average, exponential smoothing, a neural network autoregressive, a gradient-boosting regression tree, and extreme gradient boost models for infectious diseases [ 9 ]. Finally, there are supervised machine learning algorithms for lung disease detection, respiratory sound analyses, and so on [ 10 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation